"I Wanna Be a Dark‐Skinned Pork Roast" – and other stories about how 'dark' Danish rappers negotiate otherness in their marketing and music productions. Issue 2 (1st September 2014) - Ringsager, Kristine
Abstract: This article explores processes of experienced otherness as it is represented in stories told by Danish rappers with Middle Eastern background. Referring to stories about 'being stopped' the article illustrates how these rap artists, because of their visible otherness, are forced to navigate in a discursive landscape that affects their becoming of subjects as well as rap artists. The article discusses how otherness experienced in everyday encounters seems to generate habits of thought and expression, which also influence the rappers' choices regarding their music production and marketing. I propose and discuss three different ways of how this is done: (1) A strategy where rappers play along with stigmatising stories about the criminal and dangerous 'other' or 'stranger, ' hereby constituting a brand as a dangerous 'perker;' (2) a strategy where rap artists remove the danger from the stranger, hereby enabling themselves to pass as inoffensive exotic foreigners; and (3) a strategy where rappers confront the stigmatising stereotypes, creating alternative and possibly instructive stories about 'dark' Danes.